Non-coding RNAs Shaping Muscle - Martone, Julie; Mariani, Davide; Desideri, Fabio; Ballarino, Monica (Frontiers in Cell and Developmental Biology, 2020)
In 1957, Francis Crick speculated that RNA, beyond its protein-coding capacity, could have its own function. Decade after decade this theory was dramatically boosted by the discovery of new classes of noncoding RNAs (ncRNAs), including long noncoding (lnc)RNAs and circular (circ)RNAs, which play a fundamental role in the fine spatio-temporal control of multiple layers of gene expression. Recently, many of these molecules have been identified in a plethora of different tissues and they have emerged to be more cell type specific than protein coding genes. These findings shed light on how ncRNAs are involved in the precise tuning of gene regulatory mechanisms governing tissues homeostasis. In this review, we discuss the recent findings on the mechanisms used by lncRNAs and circRNAs to sustain skeletal and cardiac muscle formation, paying particular attention to the technological developments that over the last few years have aided their genome-wide identification and study. Together with lncRNAs and circRNAs, the emerging contribution of Piwi-interacting RNAs (pi)RNAs and tRNA-derived fragments (tRFs) to myogenesis will be also discussed, with a glimpse on the impact of their dysregulation in muscle disorders, such as myopathies, muscle atrophy and rhabdomyosarcoma degeneration.